2016
DOI: 10.1002/ijc.30159
|View full text |Cite
|
Sign up to set email alerts
|

Growing tumors induce a local STING dependent Type I IFN response in dendritic cells

Abstract: In this study we visualize IFN-β expression during tumor growth in a sensitive in vivo reporter system. We identify dendritic cells as major cellular source of type I IFN in tumors and demonstrate that STING and the downstream transcription factors IRF3 and IRF5 are crucial for IFN induction. The characterization of the TypeI IFN induction pathway significantly adds to the current knowledge about the involvement of TypeI IFNs in tumor development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…It was found STING-deficient mice are prone to developing several types of cancer and have poor survival under a tumor burden, whereas stimulation of STING can elicit robust immunity to tumors (225)(226)(227). A mechanism is many cancer cells expressing cGAS can recognize cytosolic DNA and produce cGAMP to stimulate secretion of type-I IFN through STING (228,229). Excessive expression of TREX1 in cancer cells, which can be induced by radiotherapy, attenuates this progression (228).…”
Section: Cgas-sting Pathway In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…It was found STING-deficient mice are prone to developing several types of cancer and have poor survival under a tumor burden, whereas stimulation of STING can elicit robust immunity to tumors (225)(226)(227). A mechanism is many cancer cells expressing cGAS can recognize cytosolic DNA and produce cGAMP to stimulate secretion of type-I IFN through STING (228,229). Excessive expression of TREX1 in cancer cells, which can be induced by radiotherapy, attenuates this progression (228).…”
Section: Cgas-sting Pathway In Cancermentioning
confidence: 99%
“…Dendritic Cells are the main source of type-I IFN in several types of TMEs and are dependent on STING signaling (229). More preferentially than macrophages, infiltrating DCs take up tumor-derived DNA or cGAMP from dying cell fragments by phagocytosis (27,29,129,226,233).…”
Section: Cgas-sting Pathway In Cancermentioning
confidence: 99%
“…Antigen presenting DC internalize tumor-derived DNA via phagocytosis of tumor cell debris [42 •• ,43 •• ], creating an IFN-I-driven autocrine loop that drives CD8+ T cell priming and activation [42 •• ,43 •• ,44 •• ,53]. Although extrinsic sensing of tumor cell debris is confined to cells with phagocytic capability, it appears that ubiquitous cell-intrinsic mechanisms exist for sensing genotoxic stress and DNA damage, which has long been appreciated as a robust inducer of the IFN-I response [54,55].…”
Section: Cancer Cancer Therapy and Genotoxic Stressmentioning
confidence: 99%
“…Although there has been considerable evidence that dendritic cells play a vital role in the anti-tumoral immune response (Andzinski et al, 2016;Carozza et al, 2020;Laursen et al, 2018), there were no differences in STING pathway activation in the presence or absence of tumor-derived extracellular cGAMP (Figure S5F), suggesting that their role in anti-tumoral immunity is downstream of a direct cGAMP responder cell. Likewise, there were no differences observed in B cells (Figure S5G).…”
Section: Intratumoral Macrophages and Nk Cells Directly Respond To Tumentioning
confidence: 96%
“…While it is known that this transfer of cGAMP ultimately results in downstream immune activation, it is unknown which cell types directly respond to tumor-derived extracellular cGAMP. Several studies have suggested that CD11c + dendritic cells are the cGAMP-sensing cells in tumors (Andzinski et al, 2016;Carozza et al, 2020;Laursen et al, 2018), while others have identified macrophages (Zhou et al, 2020b), NK cells (Marcus et al, 2018;Nicolai et al, 2020), endothelial cells (Demaria et al, 2015), and CD11b + myeloid cells (Marcus et al, 2018). However, these studies either relied on exogenous cGAMP administration or did not directly measure activation of the STING pathway in different cell types.…”
Section: Introductionmentioning
confidence: 99%